High fluorine rubber material and preparation method thereof

By adopting high fluorine rubber materials and their preparation methods, the problem of poor performance of lithium-ion battery sealing ring materials in high temperature and chemical corrosion environments is solved, the material has good chemical corrosion resistance and mechanical properties, and the processing performance and mold pollution resistance are improved.

CN119752073APending Publication Date: 2025-04-04DONGGUAN FORBETTER PLASTIC & ELECTRONICS PRODS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411865255.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium-ion battery sealing ring materials do not perform well in high temperature and chemical corrosion environments, and the processing technology is poor and it is easy to contaminate the mold.

Method used

A high fluorine rubber material is used, and the preparation raw materials include vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene terpolymer, reinforcement filler (such as barium sulfate or carbon black), internal mold release agent and vulcanizing agent, and is prepared by plasticizing, intensive refining, refining and vulcanizing molding.

Benefits of technology

This high fluorine rubber material has good acid resistance, alkali resistance and mechanical properties, improves the chemical corrosion resistance and processing properties of the seal, and avoids mold contamination.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high fluorine rubber material and a preparation method thereof. The high-fluorine rubber material is used for manufacturing a sealing element of a lithium battery, and is prepared from the following raw materials in percentage by mass: 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a crosslinking aid and 2%-5% of a vulcanizing agent, and 75% to 85% of a vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene terpolymer, wherein the reinforcing filler comprises one or two of barium sulfate or carbon black. On one hand, the reinforcing filler is selected from inert barium sulfate or carbon black and the like, so that the prepared high-fluorine rubber material has good acid resistance and alkali resistance, and the chemical corrosion resistance and the mechanical property of the high-fluorine rubber material can be improved; and on the other hand, in the processing process of the fluororubber, the internal release agent can improve the release performance, prevent mold sticking, improve the fluidity of the rubber in a mold, improve the processing performance and improve the processing efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-fluorine rubber material and a preparation method thereof. Background Art

[0002] In lithium-ion batteries, electrolyte is an important component of lithium batteries, and rubber sealing rings are used to seal the electrolyte in lithium-ion batteries. Due to the complex composition of the electrolyte, the performance requirements of the sealing ring are very high. In the prior art, the sealing ring materials used for lithium-ion batteries mainly include nitrile rubber, perfluoroether rubber, C-type fluororubber, silicone rubber and EPDM rubber. Among them, nitrile rubber is mainly used for oil seal products, and its high temperature resistance is limited, and it cannot withstand the process technology of lithium battery cover plates; although perfluoroether rubber has high reliability, it is very expensive, which is not conducive to the promotion of lithium batteries; silicone rubber has good high and low temperature resistance, but its dielectric resistance is very poor and cannot adapt to the electrolyte environment; EPDM rubber has good tolerance to electrolyte, but it is not resistant to high temperatures above 300°C, and cannot meet the assembly requirements of lithium battery cover plates. Peroxide-cured fluororubber has good chemical corrosion resistance and high temperature resistance, and is gradually used in the end face sealing of lithium battery electrolytes; however, the processing technology of peroxide-type fluororubber is poor and easy to contaminate the mold. Summary of the invention

[0003] The purpose of the present invention is to solve the above problems and provide a fluororubber and a preparation method thereof for making a seal for a lithium battery, which has good processing performance, good demoulding performance and is not easy to contaminate the mold.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0005] In a first aspect, the present invention provides a high-fluorine rubber material for making a seal for a lithium battery. The raw materials for preparing the high-fluorine rubber material include, by mass percentage, 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a cross-linking aid, 2%-5% of a vulcanizing agent, and 75%-85% of a terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene; wherein the reinforcing filler includes one or both of barium sulfate or carbon black.

[0006] Optionally, the reinforcing filler includes one or both of barium sulfate and N990 carbon black.

[0007] Optionally, the internal release agent includes Teflon powder.

[0008] Optionally, the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene includes one or more of the raw rubber model P959 or model P459 produced by Solvay Corporation of the United States, or the raw rubber model GF600S or model GF200S produced by DuPont, or the raw rubber model G925, model G922 or model G932 produced by Daikin Corporation of Japan.

[0009] Optionally, the processing aid includes one or more of fatty acids, fatty acid derivatives or waxes; the cross-linking aid includes trimethylolpropane trimethacrylate; and the vulcanizing agent includes di-25-pentane.

[0010] Optionally, the processing aid includes one or more of processing aid HT290, processing aid WS280 or wax.

[0011] In a second aspect, the present invention provides a method for preparing a high fluorine rubber material, which is used to prepare the high fluorine rubber material as described above, wherein the high fluorine rubber material is used to make a seal of a lithium battery, and the method comprises the steps of:

[0012] S1, plasticizing: plasticizing the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene at a first temperature;

[0013] S2, banburying: adding a processing aid, a reinforcing filler, an internal mold release agent, a crosslinking aid and a vulcanizing agent to the vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene terpolymer after plasticization in step S1, and banburying the mixed system at a second temperature to obtain a banburying system; wherein the reinforcing filler comprises one or both of barium sulfate and carbon black;

[0014] S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material;

[0015] S4, molding: After cooling the mixed rubber obtained in step S3 to 25-40° C., place it in a mold for vulcanization molding to obtain a high-fluorine rubber material.

[0016] Optionally, the raw materials for preparing the high fluorine rubber material include, by mass percentage, 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a cross-linking aid, 2%-5% of a vulcanizing agent, and 75%-85% of a terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene; wherein the reinforcing filler includes one or both of barium sulfate or carbon black.

[0017] Optionally, the first temperature is 25-100°C, and the plasticating time is 3-5 minutes; the second temperature is 25-120°C, and the plasticating time is 10-15 minutes, and the glue outlet temperature is 120±2°C; the third temperature is 25-70°C, and the plasticating time is 10-15 minutes.

[0018] Optionally, in step S4, the molding is carried out at a temperature of 172±5°C and a pressure of 30-200kg, and the molding time is 100-150s.

[0019] The beneficial effects produced by the present invention include at least:

[0020] The high-fluorine rubber material of the present invention is used to make a seal of a lithium-ion battery. On the one hand, it includes a reinforcing filler, and the reinforcing filler is selected from inert barium sulfate or carbon black, so that the prepared high-fluorine rubber material has good acid resistance and alkali resistance, and can improve the chemical corrosion resistance and mechanical properties of the high-fluorine rubber material; on the other hand, its preparation raw materials include an internal mold release agent, and the internal mold release agent can improve the demolding performance, prevent mold sticking, improve the fluidity of the rubber in the mold, improve the processing performance, and improve the processing efficiency during the processing of the fluorine rubber. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in the present invention. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0022] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. It should be noted that the raw materials used in the present invention can be derived from suppliers known in the art or prepared by known methods unless otherwise specified.

[0023] In the present invention, descriptions such as “first”, “second”, etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.

[0024] In a first aspect, an embodiment of the present invention provides a high-fluorine rubber material for making a seal for a lithium battery. The raw materials for preparing the high-fluorine rubber material include, by mass percentage, 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a cross-linking aid, 2%-5% of a vulcanizing agent, and 75%-85% of a terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene; wherein the reinforcing filler includes one or both of barium sulfate or carbon black.

[0025] The high-fluorine rubber material of the present invention is used to make a seal of a lithium-ion battery. On the one hand, it includes a reinforcing filler, and the reinforcing filler is selected from inert barium sulfate or carbon black, so that the prepared high-fluorine rubber material has good acid resistance and alkali resistance, and can improve the chemical corrosion resistance and mechanical properties of the high-fluorine rubber material; on the other hand, its preparation raw materials include an internal mold release agent, and the internal mold release agent can improve the demolding performance, prevent mold sticking, improve the fluidity of the rubber in the mold, improve the processing performance, and improve the processing efficiency during the processing of the fluorine rubber.

[0026] Specifically, the added amount of the processing aid can be 2% or 3%; the added amount of the reinforcing filler can be 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%; the added amount of the internal release agent can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; the added amount of the cross-linking aid can be 1%, 1.5% or 2%; the added amount of the vulcanizing agent can be 2%, 3%, 4% or 5%; the added amount of the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene can be 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84% or 85%.

[0027] Optionally, the reinforcing filler includes one or both of barium sulfate and N990 carbon black.

[0028] Optionally, the internal mold release agent includes Teflon powder. In the present invention, the internal mold release agent is a fluorine-containing mold release agent, which has low contamination on the surface of the demolded product, excellent demolding performance, good release properties for relatively viscous raw materials, low pollution to the mold, low corrosion, and effectively assists in material demolding and solves the problem of mold pollution.

[0029] Optionally, the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene includes one or more of the raw rubber model P959 or model P459 produced by Solvay Corporation of the United States, or the raw rubber model GF600S or model GF200S produced by DuPont, or the raw rubber model G925, model G922 or model G932 produced by Daikin Corporation of Japan.

[0030] Optionally, the processing aid includes one or more of fatty acids, fatty acid derivatives or waxes; the crosslinking aid includes trimethylolpropane trimethacrylate; and the vulcanizing agent includes dipentadienyl, i.e., 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0031] Optionally, the processing aid includes one or more of processing aid HT290, processing aid WS280 or wax.

[0032] In a second aspect, the present invention provides a method for preparing a high fluorine rubber material, which is used to prepare the high fluorine rubber material as described above, wherein the high fluorine rubber material is used to make a seal of a lithium battery, and the method comprises the steps of:

[0033] S1, plasticizing: plasticizing the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene at a first temperature;

[0034] S2, banburying: adding a processing aid, a reinforcing filler, an internal mold release agent, a cross-linking aid and a vulcanizing agent to the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene after plasticization in step S1, and banburying the mixed system at a second temperature to obtain a banburying system; wherein the reinforcing filler comprises one or both of barium sulfate and carbon black; during the banburying process of step S2, the remaining raw materials for preparation are added together for banburying, without adding in batches, thereby improving the preparation efficiency and reducing the power energy consumption of production.

[0035] S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material;

[0036] S4, molding: After cooling the mixed rubber obtained in step S3 to 25-40° C., place it in a mold for vulcanization molding to obtain a high-fluorine rubber material.

[0037] Optionally, the raw materials for preparing the high fluorine rubber material include, by mass percentage, 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a cross-linking aid, 2%-5% of a vulcanizing agent, and 75%-85% of a terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene; wherein the reinforcing filler includes one or both of barium sulfate or carbon black.

[0038] Optionally, the first temperature is 25-100°C, and the plasticizing time is 3-5min; based on the comprehensive consideration of the performance of the high fluorine rubber material to be prepared and the power energy consumption, the present invention preferably sets the plasticizing time to 3-5min, and within the preferred plasticizing time range, the effects of improving the plasticity of the rubber system, reducing elasticity, reducing viscosity, improving fluidity, and improving the solubility and molding adhesion of the rubber are achieved. Within the plasticizing time range of the present invention, the subsequent strength, elasticity and wear resistance will not be reduced, laying the foundation for the preparation of high fluorine rubber materials with good performance; at the same time, the power consumption of production is avoided to the greatest extent. The second temperature is 25-120°C, the mixing time is 10-15min, and the glue outlet temperature is 120±2°C; the third temperature is 25-70°C, and the refining time is 10-15min.

[0039] Optionally, in step S4, the molding is carried out at a temperature of 172±5°C and a pressure of 30-200kg, and the molding time is 100-150s.

[0040] Embodiment 1:

[0041] The high fluorine rubber material is prepared by the preparation method as described above, comprising the steps of:

[0042] S1. Plasticizing: plasticizing the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene at a first temperature; the first temperature is 25-100° C., and the plasticizing time is 3-5 minutes.

[0043] S2, banburying: adding a processing aid, a reinforcing filler, an internal mold release agent, a cross-linking aid and a vulcanizing agent to the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene after plasticization in step S1, and banburying the mixed system at a second temperature to obtain a banburying system; wherein the reinforcing filler comprises one or both of barium sulfate and carbon black; the second temperature is 25-120°C, the banburying time is 10-15min, and the discharging temperature is 120±2°C.

[0044] S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material; the third temperature is 25-70° C., and the refining time is 10-15 minutes.

[0045] S4, molding: After the mixed rubber obtained in step S3 is cooled to 25-40°C, it is placed in a mold for vulcanization molding to obtain a high-fluorine rubber material. The molding is carried out at a temperature of 172±5°C and a pressure of 30-200kg for a molding time of 100-150s.

[0046] During molding in step S4, a vulcanization curve of 177±3°C and 8 minutes is tested by a rotorless vulcanizer, and the test data are recorded as follows: T10 (i.e., scorch time) is 20-35s, and T90 (i.e., process positive vulcanization time) is 80-120s. It can be seen from the vulcanization curve that the vulcanization time obtained by the preparation method of the fluororubber of the present invention is short and easy to mold, thereby ensuring the stability of the molding of the polyurethane rubber.

[0047] The polyurethane rubber prepared in Example 1 was tested for hardness (Shore A), specific gravity, tensile strength, elongation and Mooney viscosity. The test methods are as follows: the hardness test was measured using a type A Shore durometer, and the reference standard was GB / T531 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber"; the tensile strength and elongation tests were performed using a universal tensile testing machine, and the reference standard was GB / T528 "Determination standard for tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the Mooney viscosity test condition was ML (1+4, 100°C), and the reference standard was GB / T 1232.1-2000. After testing, the properties of the high specific gravity polyurethane rubber prepared by the preparation method described above were: hardness (Shore A) was 65-75A, average specific gravity was 1.92g / cm, tensile strength was 12-15MPA, elongation was 300-450%, and Mooney viscosity was 80-90MU. In the prior art, the performance parameters of high fluororubber materials used to make seals for lithium batteries are generally: hardness (Shore A) is 70±5A, average specific gravity is 1.89±0.03g / cm, tensile strength is greater than 12MPA, and elongation is greater than 200%. This shows that the high fluororubber material obtained in the present invention can be used to make seals for lithium batteries. In addition, the raw materials for preparing the high fluororubber material of the present invention include reinforcing fillers and internal release agents. On the one hand, the reinforcing filler is selected from inert barium sulfate or carbon black, so that the obtained high fluororubber material has good acid resistance and alkali resistance, and can improve the chemical corrosion resistance and mechanical properties of the high fluororubber material; on the other hand, the internal release agent can improve the demolding performance, prevent mold sticking, improve the fluidity of the rubber in the mold, improve the processing performance, and improve the processing efficiency during the processing of the fluororubber.

[0048] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0049] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high fluorine rubber material, characterized in that: For making a seal for a lithium battery, the raw materials for preparing the high-fluorine rubber material include, by mass percentage, 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a cross-linking aid, 2%-5% of a vulcanizing agent, and 75%-85% of a terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene; wherein the reinforcing filler includes one or both of barium sulfate or carbon black.

2. The high fluorine rubber material according to claim 1, characterized in that: The reinforcing filler includes one or both of barium sulfate and N990 carbon black.

3. The high fluorine rubber material according to claim 1, characterized in that: The internal mold release agent includes Teflon powder.

4. The high fluorine rubber material according to claim 1, characterized in that: The terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene includes one or more of the raw rubber model P959 or model P459 produced by Solvay Company of the United States, or the raw rubber model GF600S or model GF200S produced by DuPont, or the raw rubber model G925, model G922 or model G932 produced by Daikin Company of Japan.

5. The high fluorine rubber material according to claim 1, characterized in that: The processing aid includes one or more of fatty acids, fatty acid derivatives or waxes; the cross-linking aid includes trimethylolpropane trimethacrylate; and the vulcanizing agent includes di-2-pentane.

6. The high fluorine rubber material according to claim 5, characterized in that: The processing aid includes one or more of processing aid HT290, processing aid WS280 or wax.

7. A method for preparing a high fluorine rubber material, characterized in that: Used to prepare the high fluorine rubber material as claimed in any one of claims 1 to 6, wherein the high fluorine rubber material is used to make a seal of a lithium battery, comprising the steps of: S1, plasticizing: plasticizing the terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene at a first temperature; S2, banburying: adding a processing aid, a reinforcing filler, an internal mold release agent, a crosslinking aid and a vulcanizing agent to the vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene terpolymer after plasticization in step S1, and banburying the mixed system at a second temperature to obtain a banburying system; wherein the reinforcing filler comprises one or both of barium sulfate and carbon black; S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material; S4, molding: After cooling the mixed rubber obtained in step S3 to 25-40° C., place it in a mold for vulcanization molding to obtain a high-fluorine rubber material.

8. The method for preparing a high fluorine rubber material according to claim 7, characterized in that: In terms of mass percentage, the raw materials for preparing the high fluorine rubber material include 2%-3% of a processing aid, 8%-15% of a reinforcing filler, 0.5%-1% of an internal release agent, 1%-2% of a cross-linking aid, 2%-5% of a vulcanizing agent, and 75%-85% of a terpolymer of vinylidene fluoride, tetrafluoroethylene and hexafluoropropylene; wherein the reinforcing filler includes one or both of barium sulfate or carbon black.

9. The method for preparing a high fluorine rubber material according to claim 7, characterized in that: The first temperature is 25-100°C, and the plasticating time is 3-5 minutes; the second temperature is 25-120°C, and the banburying time is 10-15 minutes, and the glue outlet temperature is 120±2°C; the third temperature is 25-70°C, and the refining time is 10-15 minutes.

10. The method for preparing a high fluorine rubber material according to claim 7, characterized in that: In step S4, the molding is carried out at a temperature of 172±5° C. and a pressure of 30-200 kg, and the molding time is 100-150 seconds.

Citation Information

Patent Citations

  • Rubber sealing material for hydrogen fuel cell and preparation method and application thereof

    CN110256789A

  • Insulating fluororubber material for sealing lithium battery and preparation method thereof

    CN111269511A